Health-related quality of life of Palestinian preschoolers in the Gaza Strip: a cross-sectional study - Smith Maureen; Palta Mari; Nieto F Javier; Massad Salwa G; Clark Roseanne; Thabet Abdel-Aziz (BMC, 2011)
Abstract Background Research on children's responses to wartime trauma has mostly addressed Post-Traumatic Stress Disorder (PTSD). However, PTSD is only one aspect of a complex set of responses. This study proposes to expand knowledge of well-being in children exposed to political violence through widening the conceptualization of well-being beyond PTSD, morbidity, and mortality by measuring health-related quality of life (HRQOL) and its facets, physical health, and psychosocial health. Methods In 2007, we used a cross-sectional random sample of kindergartens to examine factors associated with HRQOL, as measured by the PedsQL 4.0, in 350 preschoolers in the Gaza Strip, Palestine, where political violence and deprivation are widespread. Results About 65% of the mothers reported severely impaired psychosocial and emotional functioning in their children. Preschoolers had lower HRQOL than the US reference sample and samples of children in other low income countries with large effect size. HRQOL was comparable to those of US children with several chronic diseases. Factors associated with lower HRQOL were older child age, male gender, and more exposures to traumatic events. Factors associated with HRQOL subscales were for lower psychosocial health: older child age, history of food, water, and electricity deprivation during incursion, and witnessing assassination of people by rockets. For lower physical health: older child age, history of food, water, and electricity deprivation during incursion, and having heard of a killing of a friend by soldiers. Conclusions HRQOL, including psychosocial health and emotional functioning is often severely impaired among preschoolers in the Gaza Strip. Exposure to both violent and non-violent negative events was associated with HRQOL in preschoolers.